The use of animals in biomedical research - Hudler, Petra (Slovenian veterinary research, 2007)
Throughout the history invertebrate and vertebrate models have been used in fundamental and goal-oriented scientific research to gain new information on cell and organ anatomy, mechanisms of the diseases and methods to prevent them, behavioral research, for production, development, testing of quality andsafety of drugs, food, cosmetic and other products, and to answer scientific questions that would have been impossible to be gathered directly from humans. Although researchers are continually developing non-animal models, research on complex multigenic diseases and therapeutics testing sometimes require the use of in vivo models. It is generally recognized that in the absence of human data, animal research in many cases can offer most accurate approximations and predictions of human responses.
Keywords: Animals, Laboratory; Bolezen, živalski modeli; Disease Models, Animal; Ethics, Medical; Etika medicinska; medicinska etika; Neoplasms, Experimental; Novotvorbe eksperimentalne; poskusi; poskusne živali; raziskave; Živali laboratorijske